Are intelligence tests measurement invariant over time? Investigating the nature of the Flynn effect - Wicherts, Jelte M.; Dolan, Conor V.; Hessen, David J.; Oosterveld, Paul; van Baal, G. Caroline M.; Boomsma, Dorret I.; Span, Mark M. (Intelligence (Norwood), 2004)
The gains of scores on standardized intelligence tests (i.e., Flynn effect) have been the subject of extensive debate concerning their nature, causes, and implications. The aim of the present study is to investigate whether five intelligence tests are measurement invariant with respect to cohort. Measurement invariance implies that gains over the years can be attributed to increases in the latent variables that the tests purport to measure. The studies reported contain original data of Dutch Wechsler Adult Intelligence Scale (WAIS) gains from 1967 to 1999, Dutch Differential Aptitude Test (DAT) gains from 1984 to 1995, gains on a Dutch children intelligence test (RAKIT) from 1982 to 1993, and reanalyses of results from Must, Must, and Raudik [ Intelligence 167 (2003) 1–11] and Teasdale and Owen [ Intelligence 28 (2000) 115–120]. The results of multigroup confirmatory factor analyses clearly indicate that measurement invariance with respect to cohorts is untenable. Uniform measurement bias is observed in some, but not all subtests. The implications of these findings are discussed.